Early husbandry practices in highland areas during the Neolithic: the case of Coro Trasito cave (Huesca, Spain) - Navarrete, Vanessa; Viñerta, Angel; Clemente-Conte, Ignacio; Gassiot, Ermengol; Rey Lanaspa, Javier; Saña, Maria (Frontiers in Environmental Archaeology, 2023)
Research on animal management strategies in high mountain areas during the early Neolithic (5700-4500 cal BC) has been conditioned by the presumption that human occupations in highland areas had a prominent seasonal character and the economic practices focused mainly on the exploitation of wild resources. The results obtained in the framework of research developed recently on settlement dynamics during the early Neolithic in the highland areas indicate the existence of relatively permanent occupations and the exploitation of domestic resources. Regarding livestock, the role of caprine transhumance in highland areas has been highlighted traditionally, conferring a marginal role This is a provisional file, not the final typeset article to husbandry activities and emphasizing principally the temporary maintenance of herds of sheep and goats.In this study, we use the archaeozoological data and δ 13 C and δ 15 N stable isotopes composition of the faunal bones collagen to characterize the husbandry practices in Coro Trasito cave (Huesca, Spain). The results are discussed with an integrated analysis of the data related to animal management strategies in highland areas (more than 1500 m. asl) during the early Neolithic, in particular in the central Pyrenees area. The presence of diverse herd foddering strategies within husbandry practices characterized by taxonomic diversity and multipurpose exploitation suggests that during the Neolithic, Coro Trasito cave played a more complex role than sheepfold. Moreover, the results obtained demonstrated the adaptation of herds of Coro Trasito to the cave environment, flocks with diverse dietary needs and reproductive behaviors. This study offers new elements to study the complexity of neolithisation processes in the central Pyrenees and how these areas were quickly integrated into a broader economic system.